How Are the Reservoirs in the ApalachicolaChattahoochee-Flint River Basin Managed? - Christopher J. Martinez (EDIS)
Many uses of the Apalachicola-Chattahoochee-Flint river basin depend on how the US Army Corp of Engineers operates dam releases from the reservoirs when managing lake levels and downstream river flows and water levels. However, no single set of protocols equally suited to all uses and demands governs the reservoir releases. The purpose of this publication is to describe how the USACE manages reservoirs and dams in the ACF and how the waters in the basin are used. This 6-page fact sheet was written by Christopher J. Martinez and published by the UF Department of Agricultural and Biological Engineering, March 2013.